DMSO : nature's healer - Walker, Morton (Garden City Park, N.Y. : Avery Pub. Group, 1993)
Dr. Morton Walker in the DMSO (pain relieving drug), examined the powerful and compelling case for the use of DMSO in the treatment of many debilitating diseases and health-related problems.
Includes bibliographical references (p. 325-331) and index.
rua 23/06/14
Loans
Keywords: Dimethyl sulphoxide -- Therapeutic use